Agricultural intensification, technology adoption, and institutions in Ghana - Houssou, Nazaire; Kolavalli, Shashidhara; Silver, Jed (International Food Policy Research Institute, 2016)
Agricultural intensification has only taken off to a very limited extent in Ghana. Adoption of land productivity-enhancing technology is low, even in areas with proximity to urban markets. Rather, farmers have increasingly been adopting labor-saving technologies such as herbicides and mechanization, for which vibrant private supply channels are emerging. Further efforts to strengthen the private mechanization supply chain would help meet the rising demand for tractor services. Furthermore, mechanization could also help free up agricultural labor to perform other more labor intensive tasks.